Results of Laboratory and Field Studies on The Resistance to Verticillium Dahliae In Interspecific Hybrids - A.Sh.Ergashev; B.I. Mamarakhimov; Sh.E. Namazov; O.Kh. Sadikova; S.K. Matyakubov (American Journal of Botany and Bioengineering, 2026)
This article presents the results of laboratory and field studies on the resistance of interspecific hybrids to Verticillium dahliae. The results indicated that the breeding lines L-138/16, L-95/16, L-200/16, L-588/16, and LSG-4/06 (O-87-94) demonstrated tolerance to Verticillium dahliae Kleb in both field and laboratory conditions. These lines serve as valuable donors for developing wilt-resistant materials.